Peningkatan Pemahaman Ergonomi Tentang Posisi Duduk Yang Ergonomis Pada Siswa - Siswi SMA N 4 Takengon - Muhammad Zia Ulhaq; Alyatus Syifa Amanda; Fatimah Fatimah; Khalifa Humaira; Putriana Putriana; Rahmalia Rahmalia; Sri Mawarni; Sherina Molek; Salsa Nabila (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Ergonomics is a science that studies the interaction between humans and other elements in the form of a system, as well as a profession that practices theories, principles, data and methods in design to optimize suitability for human needs. High school students spend a lot of time at school in daily activities covering ± 6 hours with teaching and learning activities that dominate in the classroom. In the learning process students are more in a sitting position, as well as those experienced by SMA N 4 Takengon students. In this activity, the increase in knowledge in students increased by 74%.